Care and Cultural Exclusion in Restoration Spain: Transgressive Caregiving in Galdós’s Misericordia - Rodríguez, Erika (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2020)
Benito Pérez Galdós’s Misericordia (1897) represents two opposing models of providing care for diseased, disabled, or degenerate subjects: custodial care aimed at controlling social deviance and caregiving that takes into account the needs of the care recipient. I propose that, through the caregiving model, the protagonist, Benina, establishes a powerful stance against medical and economic discourses that devalued the lives of marginal subjects. This analysis examines the relationship between the categories of disease, disability, and degeneration; the role of custodial care and caregiving in the nineteenth-century Spanish economy; and how both models respond to the possibility of contagion, as well as the political implications of these responses.